CULTURAL KNOWLEDGE AND IDIORNS - Obrovol’skij, Dmitridj; Rainen, Elisabetphii (International Journal of English Studies, 2009)
The rnost salient features of conventional figurative units such as idiorns cannot be captured without addressing cultural knowledge. Underlying conceptual rnetaphors (as developed in the scope of the Cognitive Theory of Metaphor) are not the only linguistically relevant type of knowledge. In order to describe how idiorns function and to uncover their specific sernantic and pragrnatic features, one has to take into account other concepts as well, above al1 culturally based concepts which govern the inference frorn literal to figurative. Being irregular units of the lexicon idiorns cannot be sufficiently described by rnetalinguistic instrurnents designed for capturing regular rnechanisrns of rnetaphor production. What is needed is a theory specially designed to describe the irregularities of idiorns. To develop such a theory is the rnain airn of rnodern idiorn research. This paper should be viewed as a contribution to such a theory, which we label the Conventional Figurative Language Theory.